2019
DOI: 10.3390/jmse7100364
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Cyber Security Threats in a Shipboard Integrated Navigational System

Abstract: The integrated navigational system (INS) enhances the effectiveness and safety of ship navigation by providing multifunctional display on the basis of integration of at least two navigational functions, the voyage route monitoring with Electronic Chart Display and Information System (ECDIS) and collision avoidance with radar. The INS is essentially a software platform for fusion of data from the major ECDIS and radar systems with sensors for the additional navigation functions of route planning, status and dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Awan et al in Reference [26] have analyzed 59 documented accidents to better understand the vulnerabilities of Integrated Bridge System (IBS) components. Svilicic et al in Reference [27] present a study on the cyber security resilience of a shipboard Integrated Navigational System (INS) installed on a RoPax ship engaged in international trade. Wang et al in Reference [28] propose a secure relative integrated navigation method to counteract injected fault measurement attacks.…”
Section: Related Workmentioning
confidence: 99%
“…Awan et al in Reference [26] have analyzed 59 documented accidents to better understand the vulnerabilities of Integrated Bridge System (IBS) components. Svilicic et al in Reference [27] present a study on the cyber security resilience of a shipboard Integrated Navigational System (INS) installed on a RoPax ship engaged in international trade. Wang et al in Reference [28] propose a secure relative integrated navigation method to counteract injected fault measurement attacks.…”
Section: Related Workmentioning
confidence: 99%
“…The authors of [10] revealed cyber vulnerabilities of the INS on a roll-on/roll-off (RO-RO) type of vessel. The vulnerability analysis was carried out by using the Nessus Professional vulnerability scanner [39].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The INS, similarly to other marine systems on board and ashore, suffers from a number of cybersecurity vulnerabilities [10][11][12]. Further, several products have been developed to mitigate cyber threats against vessels [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The research described in [ 20 ] presents a study on the cybersecurity of integrated navigational system (INS), which interconnects ECDIS, AIS, radar systems, and other naval sensors. As in [ 13 ], the authors use a vulnerability scanner and interviews with the crew to examine the security resilience the ship.…”
Section: Related Workmentioning
confidence: 99%